THE ROLE OF NONVERBAL COMMUNICATION IN ENGLISH TEACHING - sutiyatno, sukris (TRANSFORMASI, 2015)
Classroom teaching learning activity, especially English classroom taching and learning is a kind of communication between teachers and and students. In this course both teachers and students use nonverbal and verbal to communicate consiciously and unconcisously. Teachers, especially English teachers, as a bridge to international communication and information-sender, should be strongly aware of the importance of nonverbal communication to promote the English competence of the studentsKeywords: nonverbal communication, English teach.Aktivitas pembelajaran dan pengajaran di kelas, khususnya pembelajaran dan pengajaran bahasa Inggris merupakan suatu bentuk komunikasi antara guru dan siswa. Dalam hal ini baik para guru dan siswa menggunakan komunikasi baik verbal maupun nonverbal baik secara sadar maupun tidak sadar. Pengajar bahasa Inggris seharusnya mempunyai kesadaran secara kuat terhadap pentingnya komunikasi nonverbal untuk meningkatkan kompetensi bahasa Inggris siswa.Kata kunci: komunikasi nonverbal, pengajaran bahasa Inggris